2012
DOI: 10.1103/physrevlett.109.133202
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Isolated Molecules with Ultrafast Electron Pulses

Abstract: Imaging isolated molecules in three dimensions with atomic resolution is important for elucidating complex molecular structures and intermediate states in molecular dynamics. This goal has so far remained elusive due to the random orientation of molecules in the gas phase. We show that three-dimensional structural information can be retrieved from multiple electron diffraction patterns of aligned molecules. The molecules are aligned impulsively with a femtosecond laser pulse and probed with a femtosecond elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
184
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(186 citation statements)
references
References 24 publications
1
184
0
1
Order By: Relevance
“…From these results we have approximately determined the bond distances for the three molecules and their corresponding molecular cations. Thus, the present work provides an alternative and a complement to gas-phase electron diffraction (GED) techniques, [27][28][29][30] which have been successfully used to retrieve three-dimensional structural information from molecules in the gas phase but would be difficult to apply to molecular cations.…”
Section: Introductionmentioning
confidence: 99%
“…From these results we have approximately determined the bond distances for the three molecules and their corresponding molecular cations. Thus, the present work provides an alternative and a complement to gas-phase electron diffraction (GED) techniques, [27][28][29][30] which have been successfully used to retrieve three-dimensional structural information from molecules in the gas phase but would be difficult to apply to molecular cations.…”
Section: Introductionmentioning
confidence: 99%
“…It is, however, so far not possible to experimentally produce perfectly aligned molecules in the gas phase for diffraction experiments. We have recently shown that partial alignment, achieved with a femtosecond laser pulse, is sufficient to retrieve the structure of small molecules in a field-free environment [15,16]. While it has not yet been shown that this method can be applied to large molecules, it is clear that diffraction patterns even with partial alignment provide more structural information than diffraction patterns from randomly oriented molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The first experiments showed anisotropy in the diffraction patterns when the molecules are aligned with nanosecond laser pulses [18] and when a dissociation reaction is triggered with a femtosecond UV laser pulse [19,20]. More recently, diffraction from impulsively aligned molecules has been demonstrated both with electrons [15] and with X-rays [21].…”
Section: Introductionmentioning
confidence: 99%
“…Clean molecular samples can be generated by their spatial separation according to shape [13][14][15] and size [16]. Controlling the spatial orientation of the molecules leads to an enhancement of the information that can be retrieved from a diffraction pattern, as proposed theoretically [17][18][19][20] and demonstrated experimentally for x-ray [21,22] as well as for electron diffraction [23,24]. Strong alignment or orientation is generally necessary [11,20] for three-dimensional structure reconstruction [24] and can be provided in cold supersonic molecular beams by strong-field laser alignment and mixed-field orientation [25][26][27][28][29].…”
mentioning
confidence: 99%